CERM-3726 - J. Castañer; R.T. Owen (Drugs of the Future, 1982)
Objective Naproxen has received considerable attention due to its environmental persistence and incomplete removal during wastewater treatment. This study evaluated the ovarian toxicity of naproxen at an environmentally relevant dose to assess its potential reproductive risks. Methods Female Wistar albino rats were exposed for 100 days to naproxen alone (98.39 μg/L) or to a mixture containing naproxen (98.39 μg/L), ibuprofen (117.14 μg/L), diclofenac (609.12 μg/L), and trifloxystrobin (0.04 mg/kg/day) at a 4:1:3:2 ratio. Ovarian tissues were analyzed for oxidative stress biomarkers, B-cell lymphoma 2 (Bcl-2) expression, and follicle counts. Serum was analyzed for interleukin 6 (IL-6) and progesterone concentrations. Results Compared with controls, both treated groups had a significantly higher ovary index, lower catalase activity, and lower progesterone levels, whereas body weight, malondialdehyde levels, and serum IL-6 levels did not differ significantly. Morphometric and immunohistochemical analyses demonstrated reduced preantral follicle counts and Bcl-2 expression in the treated groups. Conclusion Chronic exposure to naproxen, alone or in combination, at an environmentally relevant dose was associated with ovarian dysfunction, impaired progesterone production and antioxidant status, and disrupted ovarian follicle dynamics.